Omega-3 polyunsaturated fatty acids modify the inverse association between systemic inflammation and cardiovascular fitness. Issue 6 (June 2021) - Farley, Gabrielle; Riggs, Daniel W.; Bhatnagar, Aruni; Hellmann, Jason
Summary: Background and objective: Exercise increases quality of life and lowers all-cause mortality, likely by preventing cardiovascular disease. Although the beneficial effects of exercise are linked with reductions in chronic inflammation, individual responses vary and factors that contribute to the anti-inflammatory effects of cardiovascular fitness remain largely undefined. We sought to investigate the role of fatty acids in the inverse relationship between inflammation and cardiovascular fitness. Approach and results: In this cross-sectional study using data from 435 participants in NHANES and linear regression models with CRP as the outcome, we observed significant negative interactions between VO2 max and omega-3 polyunsaturated fatty acids (PUFAs) but not saturated, monounsaturated, or omega-6 PUFAs. When stratified by omega-3 PUFA tertiles, participants in the medium tertile, but not low tertile, show an enhanced negative association between VO2 max and CRP, with a −32.0% difference (95% CI: −44.95, −15.9%) per 10 mL/kg/min of VO2 max. Exploratory factor analysis identified five unique dietary fatty acid (FA) profiles. The FA profile consisting predominantly of omega-3 PUFA had the strongest negative association for VO2 max and CRP, with a −28.2% difference in CRP (95% CI: −43.4, −8.9) per 10 mL/kg/min of VO2 max. We also found that alpha-linolenic acid (ALA) and docosahexaenoic acid (DHA) enhanced the negative association between VO2 max and CRP, suggesting that the anti-inflammatory response to VO2 max capacity is associated with ALA and DHA levels. Males, Whites, and individuals with lower BMI were more sensitive to the effects of omega-3 PUFAs, while having high SFA levels attenuated the benefit. Conclusions: This study suggests that omega-3 PUFAs are effect modifiers for VO2 max and CRP and that the anti-inflammatory benefits of increasing cardiovascular fitness are associated with omega-3 PUFAs.